Pengaruh Electronic Word of Mouth Terhadap Purchase Intention Melalui Consumer Trust Pada Online Shop Fashion Wanita di Media Sosial Instagram (StudiPada Generasi Milenial di DKI Jakarta) - Koerniawan Hidajat; Reiza Dessy Aprianty (JOURNAL FOR BUSINESS AND ENTREPRENEURSHIP, 2019)
This study aims to determine the effect of electronic word of mouth on purchase intention through consumer trust in women's fashion shop online on social media Instagram (a study on millennial generation in DKI Jakarta). The population in this study is the millennial generation of women in DKI Jakarta, with the sampling technique being purposive sampling. The sample obtained was 100 respondents. The data obtained were analyzed using structural equating model (SEM) analysis techniques using smartPLS. Data collected with a questionnaire that has been tested for validity and reliability. The results showed that there was a significant influence of electronic word of mouth on purchase intention, there was a significant effect of electronic word of mouth on consumer trust, there was a significant influence of consumer trust on purchase intention, there was a significant effect of electronic word of mouth on purchase intention through consumer trust.Keyword : Electronic Word of Mouth, Purchase Intention, Consumer Trust